Generating of Electric Energy by a Declined Overburden Conveyor in a Continuous Surface Mine - Witold Kawalec; Robert Król (Energies, 2021)
Exploitation of lignite in continuous surface mines requires removing masses of overburden, which are hauled to a dumpsite. There are some technological arrangements where the overburden is transported several dozen meters down to a spreader operating on a lower located dumping level. Depending on an angle of a declined transportation route, there is a possibility to convert the potential gravitational energy of conveyed down overburden masses into electric energy. To recover the maximum percentage of stored energy, an energy-effective and fully loaded belt conveyor should work in a generator mode. Due to the implementation of such a solution, a lignite continuous surface mine, which is a great electric energy consumer, can obtain the status of an electricity prosumer and reduce its environmental impact, in particular demonstrating significant savings in primary energy consumption. Though lignite surface mining is phasing out in Europe, the recuperative, overburden conveyors for downhill transport match up the targets of sustainable mining, understood as getting the maximum benefits from the exploited natural resources. According to the analyzed case study, an investment into the installation of regenerative inverters for the electric power supply of the declined overburden conveyor would pay off within 3–4 years.